Parallel Lives Graeme Murphy's Swan lake for the Australian Ballet - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Graeme Murphy for the Australian Ballet. PALABRAS CLAVE: Graeme Murphy, Australian Ballet, Swan Lake.
Dentro del apartado "It's Always Swan Lake".